1925 W. Va. Acts 30-31, ch. 3, § 7(b) - (:unkn) unknown (My University, 1925)
Prohibited publicly displaying for rent or sale any revolver, pistol, dirk, Bowie knife, slungshot, other dangerous weapon, machine gun, submachine gun, or high powered rifle. Requires dealers to keep a register. Prohibited selling, renting, giving, or lending any of these weapons to an unnaturalized person.
Keywords: COMMERCIAL SALES REGULATION; MACHINE GUN RESTRICTION; REGISTRATION; TRANSFER - DANGEROUS PERSONS; TRANSFER, MANUFACTURE & POSSESSION